The Impact of FDI Inflows and ICT Development towards Economic Growth: Evidence for China and Malaysia - Norehan, Muhammad Aiman Haziq; Ridzuan, Abdul Rahim; Ismail, Shafinar; Md Razak, Mohamad Idham; Shaari, Mohd Shahidan (Business and Economic Research, 2022)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">This paper examines whether there is a long-run relationship between foreign direct investment (FDI) inflows, ICT development and economic growth in China and Malaysia. We use a newly developed cointegration test, the autoregressive distributed lag (ARDL), to examine this long-run relationship by employing annual data from 1980 to 2017. The study results show that ICT has a positive relationship with economic growth in China while negative in Malaysia. Capital and labour were found significantly influence economic growth in China and Malaysia. FDI inflows and human capital failed to influence economic growth in China, but human capital significantly influenced Malaysia. The findings are important for formulating policies by recommending mandatory policies related to FDI inflows, human capital and labour to achieve long-term and sustainable development in China and Malaysia.